PARP-1 serves as a novel molecular marker for hepatocellular carcinoma in a Southern Chinese Zhuang population. Issue 7 (July 2017) - Li, Jiatong; Dou, Dongwei; Li, Ping; Luo, Wenqi; Lv, Wenxin; Zhang, Chengdong; Song, Xiaowei; Yang, Yuan; Zhang, Yuening; Xu, Yanzhen; Xiao, Feifan; Wei, Yan; et al.
PARP-1 (poly(ADP-ribose) polymerase-1) plays an important role in tumorigenesis. Since its effects on different populations are varied, this study investigated the impact of PARP-1 on primary hepatocellular carcinoma in a Southern Chinese Zhuang population. We assessed the global PARP-1 messenger RNA expression in patients with hepatocellular carcinoma using The Cancer Genome Atlas dataset. Increased PARP-1 expression, related to alpha-fetoprotein level, was observed. The area under the receiver operating characteristic curve value was 0.833. Kaplan–Meier survival curves indicated that higher PARP-1 expression was not correlated with poorer overall survival and recurrence-free survival. In a Zhuang population, PARP-1 messenger RNA and protein levels were increased in the hepatocellular carcinoma tissue and its adjacent liver tissues as assessed by quantitative polymerase chain reaction, immunohistochemistry, and western blotting. Higher PARP-1 level was associated with a higher tumor stage (p < 0.05), without correlation with age, gender, smoking, drinking, tumor size, serum alpha-fetoprotein level, hepatitis B virus infection, metastasis, and invasion (p > 0.05). Further analysis suggested that H2AX, a PARP-1 protein interaction partner, was coordinated with PARP-1 in hepatocellular carcinoma tumorigenesis. Overall, some new characteristics of PARP-1 expression were noted in the Zhuang population. PARP-1 is a novel promising diagnostic marker for hepatocellular carcinoma in the Southern Chinese Zhuang population.